Anti-tumor effects of mevalonate pathway inhibition in ovarian cancer - Andy Göbel; Valentina M. Zinna; Stefania Dell’Endice; Nikolai Jaschke; Jan Dominik Kuhlmann; Pauline Wimberger; Tilman D. Rachner (BMC Cancer, 2020)
Abstract Background Ovarian cancer remains the most fatal gynecological malignancy. Current therapeutic options are limited due to late diagnosis in the majority of the cases, metastatic spread to the peritoneal cavity and the onset of chemo-resistance. Thus, novel therapeutic approaches are required. Statins and amino-bisphosphonates are inhibitors of the mevalonate pathway, which is a fundamental pathway of cellular metabolism, essential for cholesterol production and posttranslational protein farnesylation and geranylgeranylation. While this pathway has emerged as a promising treatment target in several human malignancies, its potential as a therapeutic approach in ovarian cancer is still not fully understood. Methods Human ovarian cancer cell lines (IGROV-1, A2780, A2780cis) were treated with increasing concentrations (0.5-100 μM) of statins (simvastatin, atorvastatin, rosuvastatin) and zoledronic acid. Effects on cell vitality and apoptosis were assessed using Cell Titer Blue®, Caspase 3/7 Glo®, clonogenic assays as well as cleaved poly (ADP-ribose) polymerase (cPARP) detection. The inhibition of the mevalonate pathway was confirmed using Western Blot of unprenylated Ras and Rap1a proteins. Quantitative real-time PCR and ELISA were used to analyze modulations on several key regulators of ovarian cancer tumorigenesis. Results The treatment of IGROV-1 and A2780 cells with statins and zoledronic acid reduced vitality (by up to 80%; p < 0.001) and induced apoptosis by up to 8-folds (p < 0.001) in a dose-dependent fashion. Rescue experiments using farnesyl pyrophosphate or geranylgeranyl pyrophosphate evidenced that blocked geranylgeranylation is the major underlying mechanism of the pro-apoptotic effects. Gene expression of the tumor-promoting cytokines and mediators, such as transforming growth factor (TGF)-β1, vascular endothelial growth factor (VEGF), interleukin (IL)-8, and IL-6 were significantly suppressed by statins and zoledronic acid by up to 90% (p < 0.001). For all readouts, simvastatin was most potent of all agents used. Cisplatin-resistant A2780cis cells showed a relative resistance to statins and zoledronic acid. However, similar to the effects in A2780 cells, simvastatin and zoledronic acid significantly induced caspase 3/7 activation (6-folds; p < 0.001). Conclusion Our in vitro findings point to promising anti-tumor effects of statins and zoledronic acid in ovarian cancer and warrant additional validation in preclinical and clinical settings.